Լյարդի մասնահատումների բարդությունները և նրանց կանխարգելումը - Բարսեղյան, Հ. Ա.; Ոսկանյան, Ա. Ա․; Հարությունյան, Հ. Վ.; Կուրղինյան, Ռ. Մ.; Վարժապետյան, Ա. Մ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Совершенствование хирургической техники и применение известных принципов профилактики за последние годы позволили снизить кровопотерю при резекции печени в 2 раза. Тщательный отбор пациентов и предоперационная эмболизация воротной вены сводят к минимуму частоту послеоперационной печеночной недостаточности. The improvement of surgical technique and the application of the above mentioned principles of prevention, in recent years, have made it possible to reduce blood loss during liver resections by 2 times. Cautious patient selection and preoperative portal vein embolization minimize the incidence of postoperative renal failure.
Keywords: Բժշկագիտություն; Առողջապահություն; Բժշկություն